(untitled) (Journal of Engineering, 2025)
Foam concrete, distinguished by its lightweight properties and versatility in construction, is a porous material produced from cement, water, fine aggregate, and foam. It contains numerous voids and lacks coarse aggregate, which accounts for its lightweight and low density. It has been widely used in roofing, partition walls, and insulation applications. This study explores an innovative approach to foam concrete production by investigating the effect of using recycled foam concrete waste, processed into various sizes of lightweight aggregate. The water-to-cement and cement-to-aggregate ratios were maintained at 0.45 and 1:1.3, respectively. The research involved replacing 50% of the aggregate volume with recycled waste from foam concrete, using specified aggregate sizes of Gradation levels of four aggregate sizes (12.5-9.50) mm, (9.50-4.75) mm (4.75-2.36) mm, and (2.36-1.18) mm. Results showed that the optimal size for use was 9.50-4.75 mm, which enhanced compressive strength, and tensile strength while increasing water absorption at 28 days by percentages compared to traditional FC mix. The study aims to minimize the use of natural aggregate resources and reduce construction waste. Through a comprehensive experimental program including material characterization, and mechanical performance testing, the findings are expected to provide valuable contributions to sustainable construction practices.